BEDNAREK, Monika y MARTIN, Jim R. (eds.) (2010). New Discourse on Language. Functional Perspectives on Multimodality, Identity, and Affiliation - Alvarado, Damián (Revista Latinoamericana de Estudios del Discurso, 2020)
BEDNAREK, Monika y MARTIN, Jim R. (eds.) (2010). New Discourse on Language. Functional Perspectives on Multimodality, Identity, and Affiliation. London: Continuum. 269 pp. ISBN 978-1-8470-6483-7.